The Impact of Delivery Methods on the Delivery Outcomes of Women with a Prolonged Second Stage and a Fetus in the Occipital Posterior Position - Jun Zhou; Shengyan Mao; Zhaoping Zheng; Chunxia Lin; Jia Tang; Jie Lin; Jie Ling; Lixi Yang; Zijuan Jiang; Dandan Wu (Clinical and Experimental Obstetrics & Gynecology)
Background: The objective was to explore the impact of different delivery methods on maternal and infant outcomes in women with a prolonged second stage of labor and a fetus with a persistent occipital posterior position. Methods: 60 women with a fetus in the occipital posterior position who underwent obstetric low forceps-assisted delivery were selected as the study group according to the order of delivery, and 40 women who underwent cesarean section during the same period were selected as study group 1 according to the order of delivery. We compared the maternal-related indicators and neonatal outcome-related indicators of the two groups. Then, we selected women in chronological order during the same period to be included in control group 2 (60 primiparous women with a fetus in the occipital anterior position who underwent low forceps-assisted delivery during the same period) for comparison with the study group. Results: The time of fetal head delivery, postpartum hemorrhage rate, hospitalization time, average hospitalization cost, and number of cases of postpartum infection in the group with a fetus in the occipital posterior position and low forceps-assisted delivery were significantly lower than those in the cesarean section group (p < 0.05). There was no statistically significant difference in the 1-minute Apgar score, umbilical artery blood gas pH value, or number of neonatal injuries between the cesarean section group and the group with a fetus in the occipital posterior position with forceps-assisted delivery (p > 0.05). There were also no statistically significant differences in the complication-related indicators between the group with a fetus in the occipital posterior position with forceps-assisted delivery and the group with a fetus in the occipital anterior position with forceps-assisted delivery. The two groups had second-degree lacerations, cervical lacerations, vaginal wall lacerations, and vaginal wall hematomas. There was no statistically significant difference in the comparison of urinary retention (p > 0.05), and there was no statistically significant difference between the group with a fetus in the occipital posterior position and forceps-assisted delivery and the group with a fetus in the occipital anterior position and forceps-assisted delivery in the comparison of related indicators of neonatal outcomes and pelvic floor reexamination at the Aa and Ap points 42 days after delivery (p > 0.05). Conclusions: The use of low forceps for women with a prolonged second stage of labor and a fetus in a persistent occipital posterior position can effectively shorten the time of fetal head delivery, reduce postpartum bleeding, reduce the incidence of postpartum infection, shorten the hospitalization time, and reduce average hospitalization costs and does not increase adverse neonatal outcomes.